Knowledge of Health Care Providers on HPV Related Issues in Cervical Cancer (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Background: The field of cervical cancer prevention is  rapidly evolving because of identification of Human  Papilloma Virus (HPV) as the necessary cause of disease.  HPV vaccines are now in the market. For successful  triggering of cervical cancer prevention program, HPV  informations should be communicated to health care  providers whose understanding about HPV has lagged  behind the scientific and technical advances.Objective: The objective of this intervention study was to  identify gap and educate health care providers delivering  services to women and adolescents in Medical Colleges on  HPV related issues and vaccination.Methods: The study was done from July 2007 to June 2008  where 3 advocacy workshops were conducted. The  knowledge level of 106 participants were assessed before  and after intervention. Updated informations about HPV  and vaccine was given to participants as intervention.Results: Wide knowledge gap was identified among  participants on HPV related insues, but significant  improvement was observed following intervention. The  pretest and post test score of knowledge was 28.09 and 38.60  respectively showing an average increase of 10 after  intervention.Conclusions: HPV education should be extensively  disseminated to health care providers to obtain public health  benefits of HPV vaccination program. DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11329 J Bangladesh Coll Phys Surg 2011; 29: 213-218